A comparison of supervised and rule-based object-orientated classification for forest mapping - Stephenson, Garth Roy (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2010.